Internationalization vs. Localization: The Translation of Videogame Advertising - de Pedro Ricoy, Raquel (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractA study of the translation of advertising material cannot be restricted to the analysis of language transfer, as the effectiveness of advertisements is contingent upon the successful linkage of (audio)visual elements, media of dissemination and written text. This paper analyses the cross-cultural dissemination of advertisements for the video-game industry, examining commercial arguments from a linguistic and cultural perspective. It is posited here that, in spite of their apparent disparity, the disciplines of translation theory and marketing interface to a large extent in the context of cross-cultural advertising. In the global marketplace, multinationals are faced with the choice to either internationalize or localize the promotion of their products, an issue that mirrors the long-standing debate on naturalising (or domesticating) vs. foreignizing translation strategies. The conclusion reached is that the cross-cultural dissemination of advertising material is best served by adopting an instrumental approach to translation, as described by Nord (1989).